PSYCHOLOGICAL DETERMINANTS OF DECISION MAKING - Korokhod, Yasmina (PSYCHOLOGICAL JOURNAL, 2020)
The article reviews several provisions of the psychological theory of decision making. The materials considered in the article indicate that decision-making is a complex mental process that covers a wide range of issues related to human behaviour in solving personal and business problems. The modern theory of decision-making consists of two relatively independent parts – the normative and psychological theories of decisions. Each of them plays a specific role: the normative (or precriptive) theory offers special decision-making methods, and the psychological (or descriptive) theory describes the real behaviour of people in situations of choices and reveals the psychological mechanisms of decision making. The author analyzed descriptive decision-making models, namely: the concept of limited rationality, the theory of prospectuses, the theory of remorse, and strategies for multi-criteria choices. The multi-criteria selection strategies, in turn, are divided into two groups, which are also investigated in the article; these are compensation strategies and exclusion strategies. Compensation strategies are used when people seek to compare the advantages and disadvantages of each alternative in order to compare them with each other and choose the best. These include the additive strategy, the additive difference strategy, and the ideal point strategy, which are also highlighted in the article. The second group, exclusion strategies, also called non-compensating strategies, was studied also. Exclusion strategies are used in cases where people refuse to compare the advantages and disadvantages of all alternatives and apply simple heuristic rules to exclude from consideration some options as “not worthy of attention” and leave a small number of alternatives from which a reasonable choice can be made. The article reveals the essence of strategies that belong to this group, namely: dominance strategy, conjunctive strategy, disjunctive strategy, lexicographic strategy and tactics of exclusion by aspects. The research field chosen by the author became a platform to determine the content of the psychological characteristics of decision-making, which were presented in the article. The examined questions do not exhaust the entire content of the psychological theory of decision-making, but help to form general ideas on this theory, its problems and developmental prospects.